2021
DOI: 10.1021/acs.jpclett.1c01383
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Probe of the Hydrogen Bond Network in Aqueous Glycerol Aerosols

Abstract: The properties of aerosols are of paramount importance in atmospheric chemistry and human health.The hydrogen bond network of glycerol-water aerosols generated from an aqueous solution with different mixing ratios, is probed directly with X-ray photoelectron spectroscopy. The carbon and oxygen X-ray spectra reveal contributions from gas and condensed phase components of the aerosol.It is shown that water suppresses glycerol evaporation up to a critical mixing ratio. A dielectric analysis using terahertz spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…The THz spectrum of the solute and its hydration shell is obtained by subtracting the volume‐scaled absorption spectrum of bulk water from the absorption spectrum of a solution containing the solute of interest [27, 31] . Hydration‐shell vibrational spectroscopies provide valuable information on the intermolecular interactions involving the solute and its hydration water molecules [31, 35–37] . In our previous studies we focused on the HB intermolecular stretching region (100–300 cm −1 ), i.e.…”
Section: Figurementioning
confidence: 99%
“…The THz spectrum of the solute and its hydration shell is obtained by subtracting the volume‐scaled absorption spectrum of bulk water from the absorption spectrum of a solution containing the solute of interest [27, 31] . Hydration‐shell vibrational spectroscopies provide valuable information on the intermolecular interactions involving the solute and its hydration water molecules [31, 35–37] . In our previous studies we focused on the HB intermolecular stretching region (100–300 cm −1 ), i.e.…”
Section: Figurementioning
confidence: 99%
“…[27,31] Hydration-shell vibrational spectroscopies provide valuable information on the intermolecular interactions involving the solute and its hydration water molecules. [31,[35][36][37] In our previous studies we focused on the HB intermolecular stretching region (100-300 cm À 1 ), i.e. the low frequency region showing the collective vibrations of the water HBnetwork, and we were able to identify two characteristic bands of the HB-network in the alcohol hydration layer.…”
mentioning
confidence: 99%
“…Recently, a molecular level picture of the hydrogen bond network was revealed using X-ray photoelectron spectroscopy of aqueous glycerol aerosols in conjunction with IR and THz spectroscopies of mixed solutions. 15 Therein, it was shown that upon increasing the glycerol content, the hydrogen bond network evolved from glycerol molecules being surrounded by water forming a solvated water network toward one where water is confined within glycerol's hydrogen bond network. Beyond a mole fraction of 22% glycerol, the aerosols resembled bulk glycerol.…”
Section: ■ Introductionmentioning
confidence: 99%